“Devdan Show” Dalam Perspektif Seni Pertunjukan Pariwisata - I Putu Bagus Bang Sada Graha Saputra (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2020)
Devdan is one of the performing arts performance industries that is able to attract enthusiastic tourists both domestic and international, through its spectacular dance performances. The presence of Devdan Show as a tourism performance art, can be said to bring fresh air to the atmosphere of performing arts in Bali. A good managerial system, high quality standards in terms of dances and performances, and a great sense of concern for its employees, make Devdan Show one of the performing arts industries that can be used as an example for the development and preservation of tourism-based cultural arts in Indonesia. The method used to research Devdan Show is a qualitative research method with direct observation and interview techniques. In the perspective of tourism performing arts, there are 4 important things that can be used to discuss the content presented by Devdan Show, including: 1). Performance form; 2). Audience society; 3). Dancers or talents; and 4). Rewards or awards. Devdan Show as a performing art can be said to be a forum for art development. Thus, art, which is one of the elements of culture, is expected not to give inner satisfaction to art actors and tourists, but at the same time it can improve people's lives through the tourism industry. Through the tourism industry, performing arts, and dance in Bali, it is not only able to fulfill the need for beauty, but in fact it is able to provide prosperity as well as improve the standard of life for performing arts actors in Bali. Keywords: Devdan Show, Tourism performing arts.